Effect of 8-week of dietary micronutrient supplementation on gene expression in elite handball athletes - Molina-López, J.; Quispe Ricalde, M. A.; Valladares Hernández, B.; Planells, A.; Otero, R.; Planells, E. (PLOS ONE, 2020)
Purpose: A study was made of the changes in gene expression in elite handball athletes, comparing gene modulation before, after and in the absence of an 8-week nutritional intervention with multivitamin/mineral supplements. Methods: Thirteen elite handball athletes (aged 22.9 ± 2.7 years) and 13 sedentary controls (aged 20.9 ± 2.8 years) were included. Three timepoints were established: T0 (baseline conditions); T8 (after 8 weeks of supplementation with a multivitamin/mineral complex); and T16 (after 8 weeks in the absence of supplementation). The expressions of a total 112 of genes were evaluated by RT-qPCR analysis with the QuantStudioTM 12K Flex Real-Time PCR System. Results: The analysis revealed different gene regulation profiles of genes implicated in cell communication, cell energy metabolism, inflammation and the immune system, oxidative stress and muscle function in athletes compared to sedentary controls under resting conditions (upregulated genes: effect size = large, Eta2 = 1.011 to 1.398, p < 0.05; downregulated genes: effect size = large, Eta2 = 0.846 and 1.070, p < 0.05, respectively). The nutritional intervention encouraged gene upregulation in elite athletes (p < 0.05). In a follow-up investigation, the IRAK1, CD81, ITGB1, ACADS PDHA2 and GPX1 genes were downregulated in athletes, with a moderate main effect for time-by-group interaction (?P2 = 0.099 to 0.133; p < 0.05). Additionally, nutritional genes such as MTHFR and THTPA revealed a moderate effect over all the timepoints and group interaction in the study (EtaP2 = 0.070 to 0.092; p < 0.05). Conclusions: Elite handball athletes showed a different expression profile in reference to key genes implicated in several sports performance-related functions compared to the sedentary controls, in addition to modulation of gene expression after multivitamin/mineral supplementation.